2019
DOI: 10.1080/15592324.2019.1690724
|View full text |Cite
|
Sign up to set email alerts
|

BES1 directly binds to the promoter of the ACC oxidase 1 gene to regulate gravitropic response in the roots ofArabidopsis thaliana

Abstract: Brassinosteroids (BRs) are known to be endogenous regulators of ethylene production, suggesting that some BR activity in plant growth and development is associated with ethylene. Here, we demonstrated that ethylene production in Arabidopsis thaliana roots is increased by BR signaling via the ethylene biosynthetic gene for ACC oxidase 1 (ACO1). Electrophoretic mobility shift and chromatin immuneprecipitation assays showed that the BR transcription factor BES1 directly binds to two E-box sequences located in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 50 publications
0
4
0
Order By: Relevance
“…Furthermore, cytokinins activate tissue-specific expression of ACO2 , ACO3 and ACO4 in Arabidopsis roots leading to an inhibition of primary root growth (Yamoune et al ., 2023). Brassinosteroids activate ACO1 expression in the root tip via BES1, and contribute to the regulation of a gravitropic response (Park et al ., 2020). Oppositely, brassinosteroids inhibit ethylene production in the shoots by down regulating ACO2 and ACO4 expression directly via the transcription factor BES1 and BZR1 respectively (Moon et al ., 2020; Moon et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, cytokinins activate tissue-specific expression of ACO2 , ACO3 and ACO4 in Arabidopsis roots leading to an inhibition of primary root growth (Yamoune et al ., 2023). Brassinosteroids activate ACO1 expression in the root tip via BES1, and contribute to the regulation of a gravitropic response (Park et al ., 2020). Oppositely, brassinosteroids inhibit ethylene production in the shoots by down regulating ACO2 and ACO4 expression directly via the transcription factor BES1 and BZR1 respectively (Moon et al ., 2020; Moon et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…In Arabidopsis seedlings, AtBZR1 negatively regulates AtACO4 expression by binding to the BRRE-box in its promoter (Moon et al, 2020). By contrast, AtBES1 and AtBZR2 increase ethylene production for gravitropism by directly binding to the E-boxes of the AtACO1 promoter in Arabidopsis roots (Park et al, 2020). In this study, SlBZR1 and SlBES1, as a transcriptional activator and repressor, respectively, promoted tomato fruit ripening by increasing SlBZR1 promotes fruit ripening and carotenoid accumulation Journal of Integrative Plant Biology ethylene biosynthesis and carotenoid contents, and inhibiting pectin de-methylesterification, respectively.…”
Section: Slbzr1 and Slbes1 Function Redundantly In Tomato Fruit Ripen...mentioning
confidence: 99%
“…In this study, SlBZR1 and SlBES1, the homologous gene of This study showed that SlBZR1 positively regulated the expression of SlACO1, SlACO3 and SlPSY1 by directly binding to the E-boxes in the promoters of these genes during tomato fruit ripening (Figure 4 and 5). Similarly, in Arabidopsis roots, BES1/BZR2 increase ethylene production for gravitropism by directly binding to the E-boxes in the promoter of ACO1 [71]. In contrast, BZR1 negatively regulates ACO4 expression by binding to the BRRE-box of the ACO4 promoter in arabidopsis seedlings [72].…”
Section: Slbzr1 and Slbes1 Function Redundantly In Tomato Fruit Ripen...mentioning
confidence: 99%